Lineal structures in the dictionaries of Spanish synonyms and antonyms - Martinez Real, Francisco (Romanica Olomucensia, 2016)
This article presents an analysis of the linear structures - proposed by Cruse (2000) and accepted among most linguists - in different dictionaries of Spanish synonyms and antonyms. The article first explains the concept of linear structures and its implications for the elaboration of dictionaries. It then explores if these structures are reflected in the dictionaries and in which ways these structures can help to improve dictionary entries of this kind by clarifying which words can be classified as synonyms and antonyms.
Keywords: antonym; dictionary; lexicography; linear structures; synonym.